2012
DOI: 10.1016/j.molcel.2012.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Machinery for Insertion of Tail-Anchored Membrane Proteins into the Endoplasmic Reticulum Membrane in Mammalian Cells

Abstract: Tail-anchored (TA) membrane proteins destined for the secretory pathway are posttranslationally inserted into the endoplasmic reticulum (ER) membrane, but the molecular machinery for this insertion in mammalian cells remains elusive. Here we reveal a mammalian protein complex that drives the membrane insertion. We identify calcium-modulating cyclophilin ligand (CAML) as a mammal-specific receptor for TRC40, an ATPase targeting newly synthesized TA proteins, and show that CAML mediates membrane insertion of TA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
160
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(166 citation statements)
references
References 42 publications
5
160
0
1
Order By: Relevance
“…The final component, TRC40, was generated as a N-terminal GST tag (GST-TRC40) (Fig. S1B), as done previously (44,45). Transfer was initiated by incubation of hSGTA/MBP-Sbh1 either with GST-TRC40 alone or with the Bag6 min complex (Fig.…”
Section: The Bag6 Min Complex Is An Independent Module That Facilitatmentioning
confidence: 99%
“…The final component, TRC40, was generated as a N-terminal GST tag (GST-TRC40) (Fig. S1B), as done previously (44,45). Transfer was initiated by incubation of hSGTA/MBP-Sbh1 either with GST-TRC40 alone or with the Bag6 min complex (Fig.…”
Section: The Bag6 Min Complex Is An Independent Module That Facilitatmentioning
confidence: 99%
“…The GET complex has been suggested to genetically associate with endomembrane trafficking pathways (10,11), and inactivation of the GET pathway results in ER stress and activation of the UPR (12). Mechanistic studies, primarily in cell-free systems, have suggested a role for Get3 and the mammalian homolog Asna1 (also known as TRC40) in delivering tail-anchored (TA) proteins for posttranslational insertion into the ER through the CAML/WRB receptor complex (13)(14)(15)(16). In agreement with the proposed role for the GET/TRC pathway in membrane trafficking within the secretory pathway, key regulators of membrane-mediated transport and protein translocation (e.g., soluble NSF attachment protein receptors [SNAREs] such as Sec22b and Sed5 as well as Sec61b and RAMP4) have been proposed as protein clients for this pathway (17).…”
mentioning
confidence: 99%
“…To examine its role in the insertion of the tail anchor of PTP1B, we systematically deleted proteins involved in this pathway in a yeast strain chromosomally expressing yemCitrine-PTP1Btail. Deletions of ER-resident Get2 (functional mammalian homologue CAML 60 ), cytosolic chaperone Get3 (mammalian homologue TRC40 16 ), the chaperone-interacting protein Sgt2 (mammalian homologue SGTA 61 ), and/or the ER-resident Get1 (mammalian homologue WRB 62 ) led to the formation of cytosolic aggregates, indicating the involvement of the GET pathway. Similar aggregates were observed under the same experimental conditions for the tail anchors of Ysy6 and Sec22, which were previously identified as GET pathway targets using the same phenotypic assay 17,19 .…”
Section: Investigation Of Tail Anchor Targeting Pathways That May Regmentioning
confidence: 99%